Julius Martov (1873–1923) and modern Russian historiography - A.A. Salnikova; V.V. Astafiev (Ученые записки Казанского университета: Серия Гуманитарные науки)
This article analyzes the current state of Russian historiography of the development of Menshevism in Russia. Particular attention is paid to A.L. Litvin and I.Kh. Urilov’s monograph “Julius Martov. A History of Life and Work. 1873–1923” published in 2021. This is a historical and biographical study of Julius Osipovich Martov (Tsederbaum), one of the most prominent figures in the socio-political life of Russia during the late 19th–the first quarter of the 20th centuries. Using a broad range of historical sources, including personal ones (such as the Ju.O. Martov Collection at the Russian State Archive of Social and Political History, Ju.O. Martov’s memoirs (“Notes of a Social Democrat” (1924)), as well as the memoirs of his relatives, friends, colleagues, and political opponents), we managed to comprehensively cover all aspects of the life and work of Ju.O. Martov as an extraordinary person and politician, one of the strongest leaders of social democracy in Russia, and the closest associate of V.I. Lenin and G.V. Plekhanov. The approaches to studying the origins and evolution of Ju.O. Martov’s views on the role played by the social democratic party in the history of Russia, his political and moral assessment of the essence and prospects of the Bolshevist regime, its influence on the struggle for a democratic future of the country were discussed. The place occupied by the monograph under consideration in modern Russian historiography of the problem was identified.